The shock response of biomaterials - Fitzmaurice, Brianna C. (Cranfield University, 2018)
The shock response of microorganisms is of particular interest to many different areas of research including, but not limited to: asteroid and meteoritic impacts and origins of life; food sterilisation; and deep-sea organisms. The primary interest behind the investigation presented in this thesis is the origins of life and how, if life began elsewhere in the universe, it could survive transfer from one planetary body to the next. This ties in with the theory of panspermia and suggests that life on Earth, or its building blocks, may have originated elsewhere in the universe and was transferred here via an asteroid or meteor. Aside from the many other caveats that travel through space would present to an organism, such as extreme temperatures and ionising radiation, to survive a meteoritic impact onto a planetary body would be to survive extreme shock pressures as well. The purpose of this investigation, therefore, was to examine a number of organisms under quasi-one-dimensional shock loading conditions in order to assess the organisms’ response to shock pressure. The microorganisms chosen were Escherichia coli NCTC 10538 and Saccharomyces cerevisiae ATCC 18824, two model organisms, a prokaryote and a eukaryote, respectively, whose biochemistry is well characterised. The shock loading experiments were carried out in a 50 mm bore single stage gas gun using the plateimpact technique. The bio-samples were contained within a capsule system that allowed them to be safely contained and retrieved after the shock so that their growth rates could be assessed. E. coli was subjected to shock pressures ranging from 0.55 to 10 GPa under various different shock conditions, yielding growth rates of 6% to 0.09%, respectively. S. cerevisiae was shock loaded to from 0.49 to 2.33 GPa with resulting growth rates ranging from 1.8% to zero growth. Additionally, to probe further into how life forms of varying complexity might respond to these shock pressures, the multicellular organism, Artemia salina, was shock loaded under the same conditions, but only up to a maximum pressure of 1.5 GPa. It was noted that Artemia cysts showed hatching rates of up to 18% at this pressure, but this was not always without residual damage to the shell and the embryo within. Since pressure gauges could not be attached to the target capsule due to the complexity of the set-up, validated numerical models had to be employed to interrogate the pressures occurring within the sample. This also gave an indication as to the type of loading occurring within the sample. It was also desired to measure temperatures occurring during shock loading and to explore methods to better control this so that samples could be shocked to a particular pressure, while still controlling temperature. This was achieved using a novel type of flyer plate called Surfi-Sculpt® while validated numerical models were again used to estimate peak temperatures inside the capsule containing the biological sample. From the findings of a variety of shock experiments carried out throughout this project, a number of mechanisms were proposed to explain some of the results seen, providing insight into how microorganisms in particular might survive high shock pressures.
© Cranfield University, 2018
Keywords: Shock loading; Plate-impact; Escherichia-coli